2009
DOI: 10.1039/b816345f
|View full text |Cite
|
Sign up to set email alerts
|

Precursor-directed biosynthesis of fluorinated iturin A in Bacillus spp.

Abstract: Some iturin A-producing strains of Bacillus subtilis will elaborate the novel fluorinated analogue when incubated with 3-fluoro-L-tyrosine. The activity of iturin A is dependent on the D-tyrosine residue and the presence of fluorotyrosine may result in an improvement of the biological properties of this lipopeptide. The fluorinated iturin might also be used as a probe for studying its interaction with biological membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 17 publications
2
30
0
1
Order By: Relevance
“…The PCR analysis further confirms the presence of ItuD and SrfC lipopeptide genes in isolate YSPMK11 which were responsible for the antifungal activities. Iturin A has reported to have strong haemolytic activity which kills wide range of fungal phytopathogens, whereas surfactin help in swarming, cell spreading, and biofilm production which favours the bacteria to colonize the root cells of plants (Moran et al 2009;Yuan et al 2011). In this study, we also found the potential antifungal compounds produced by B. pumilus.…”
Section: Discussionsupporting
confidence: 59%
“…The PCR analysis further confirms the presence of ItuD and SrfC lipopeptide genes in isolate YSPMK11 which were responsible for the antifungal activities. Iturin A has reported to have strong haemolytic activity which kills wide range of fungal phytopathogens, whereas surfactin help in swarming, cell spreading, and biofilm production which favours the bacteria to colonize the root cells of plants (Moran et al 2009;Yuan et al 2011). In this study, we also found the potential antifungal compounds produced by B. pumilus.…”
Section: Discussionsupporting
confidence: 59%
“…The flow rate and the temperature of the column was optimized by using standard Iturin A >90% (Sigma Aldrich, Canada) to allow for appropriate separation of iturin A from any impurities. Standard curve was made by running different concentrations of standard iturin A (10,20,30,40,50,60,70,80, 90 and 100 ppm). The optimized flow rate was 1.0 mL/min and temperature of column compartment was set at 25°C with injection volume of 10 μL.…”
Section: Quantification Of Iturin a By Liquid Chromatographymentioning
confidence: 99%
“…The growth inhibitory effects caused by NCAAs, which have been demonstrated in different species including bacteria [65,66,67], yeasts [68], insects [69,70], and mammals [71], comprise one major challenge encountered during genetic code modification. The inhibitory effects of NCAAs are mainly attributable to two aspects.…”
Section: Challenges Of Genetic Code Engineeringmentioning
confidence: 99%